Intervention Of Nurse Deficit Self Care In The Skizofrenia Patient: Systematic Review - Rosmini; Sutria, Eny; Wahdaniah (Journal Of Nursing Practice, 2020)
Background: Schizophrenia is one of the disorders in the brain that causes difficulties in processing information, solving problems and interpersonal relationships, due to interference with brain function. Patients who experience mental disorders, especially patients with schizophrenia, have decreased while doing the Daily Living Activity (ADL) because of apathy and loss of motivation means loss of interest and energy in life. This causes the patient to experience a decrease in productivity. Schizophrenia in an apathetic state experiences the disruption of daily activities such as brushing teeth, combing hair, bathing, dressing / dressing up or ignoring eccentric neatness or ignoring hygiene so intervention is needed to overcome the problems experienced.Purpose: This study aimed to find out how nursing interventions self-care deficits in schizophrenic patients.Methods: The design of this research is quantitative descriptive with a systematic review approach that has the criteria for reviewing the article carried out in a structured and planned manner.Results: Research results from the six journals analyzed nursing interventions for self-care deficits in schizophrenic patients improve personal hygiene.Conclusion: The results of this study indicate that nursing interventions for self-care deficits in schizophrenic patients are supportive group therapy, daily schedule of activities, health education, group activity therapy, motion rehabilitation, and motivation for group art therapy.